Effectiveness of Wastewater Treatment Plant (WWTP) on Domestic Wastewater Parameters at the Colonel H.M Syukur Regional Mental Hospital, Jambi - Dwi Suraini, Dhea; Damris, Damris; Rosyani, Rosyani (Rifa'Institute, 2025)
Introduction: Wastewater management at the Colonel H.M. Syukur Jambi Regional Mental Hospital is a crucial concern for maintaining environmental sustainability and public health. This is based on the quality standards established by the Minister of Environment and Forestry Regulation No. 68 of 2016. Purpose: analyzing the effectiveness of the wastewater treatment plant (WWTP) at the Colonel H.M Syukur Jambi Regional Mental Hospital and examining the relationship between inlet and outlet wastewater parameters using the product moment correlation test. Method: Data was obtained from periodic laboratory testing and secondary data from the hospital, using descriptive analysis as the method. Results and Discussion: The wastewater treatment plant (WWTP) at the Kol. H.M. Syukur Regional Mental Hospital in Jambi is quite effective, with a value of 80-89% in reducing pollutant levels, with some parameters meeting the established quality standards. Correlation tests show a relationship between COD and BOD, and oil and fat parameters with ammonia. Conclusion: there is a significant relationship between the inlet and outlet that supports the success of the processing process.